Refine understanding and mobilize consistent policies to address early school leaving - Escudero Muñoz, Juan Manuel; Rodríguez Entrena, María Jesús (Avances en Supervisión Educativa, 2011)
Early school leaving, one of the objective more relevant in the Spanish educational system and in the European context, should be understood in a straight relationship with risks and school failure in compulsory education.  Usual and big indicators analysis need to be complemented with the visibility of another data and evidences concerning the educational administration and policy, the school organization governance, the official curriculum and the real teaching and learning practices in different contexts. It´s necessary in order to more illuminative and founded the educational policies in these areas, so as more coherent and integrated. Some conclusions of research related to some the specific programs for students at risk in the Spanish educational system are presented and proclaimed that, in order to prevent and deal with school failure and early school leaving a varied set of decisions have to be taken at the level of the school, teachers and educational administration and policy.